Biblioteka Uniwersytecka w Poznaniu i Biblioteka Poznańskiego Towarzystwa Przyjaciół Nauk w latach 1919-1953. Od współpracy do przyjaznego współistnienia - Głowacka-Helak, Małgorzata (Biblioteka Uniwersytecka w Poznaniu, 2007)
The article recalls an important episode in the history of the two distinguished libraries in the region. When, in 1919, the new Polish university in Poznań was established it did not have a matching library for the purposes and aspirations of a newly-established academic institution. When the former Kaiser Wilhelm Bibliothek was converted into the University Library it could not initially manage the task as its collections almost did not include many sought-after Polish books. The problem was finally resolved by a decision to co-operate closely with the library of the Society of the Friends of Sciences. In return for some financial support (some of the librarians working in the library were included the University salary grid), the library of the Society undertook to made its collections available to the University staff and students. This was of utmost importance as the University Library, especially in the first years of its existence, suffered from painful shortages in copies of Polish books, and this opportunity helped the University to cope with the teething problems and provide its students with good studying conditions.
Poznań University Library and the Library of the Poznań Society of the Friends of Sciences in the years 1919-1953